Batbuyan Batjav's research comments on Mongolia, November 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2021)
Each province is differentiated in the text by font colors
Keywords: Arid regions; Weather; Schools; Youth; Prices; Herders; Food security; Communication; Local government; Lockdown; Mongolia; Funeral Custom; Funeral Rite; COVID-19 Pandemic